Efforts to Improve Teacher Competence With the Implementation of A Pesantren-Based Multiple Intellegences-Based Learning Model - Munzaini, Muhammad; Amirudin, Yoyok (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
The purpose of this Best Practices study was to improve teacher competence by implementing a multiple intellegences-based learning model at Bina Insani Islamic Junior High School Susukan Pesantren-Based School. The type of research used is qualitative with a descriptive approach. Data were collected through in-depth interviews, participatory observation, and document review. The collected data were analysed using qualitative data analysis techniques. The results show that the application of multiple intelligences at Bina Insani Susukan Islamic Junior High School involves three stages, namely input, process, and output. Input involves preparing students to face new challenges and applying multiple intelligence research (MIR). The output includes learning from the learning process, focusing on cognitive, psychomotor, and effective skills. Evaluation involves consultation, observation, and feedback to understand the quality of the plan and the effectiveness of the learning process. However, the application of multiple intelligence in Pondok Pesantren Bina Insani Susukan is still conservative/traditional, although it has developed various sports teams and clubs. The overall learning approach in this school lacks a comprehensive and structured approach.